Effect of Ratio of Pineapple with Broccoli and Arabic Gum Concentration on the Quality of Fruit Leather - Resti Juniarti Nainggolan; Linda Masniary Lubis; Zulkifli Lubis (Jurnal Rekayasa Pangan dan Pertanian, 2015)
The aim of this research was to find the effect of ratio of pineapple with broccoli pulps and several arabic gum concentration on the quality of pineapple and broccoli mixture fruit leather. This research was conducted at the Laboratory of Food Technology, Faculty of Agriculture, University of Sumatera Utara, Medan, using completely randomized design with two factors, i.e.:ratio of  pineapple with broccoli pulps (B): (65%:35% ; 60%:40% ; 55%:45% ; 50%:50%) and arabic gum concentration (G): (0,6% ; 0,8% ; 1,0% ; 1,2%). Parameters analyzed were moisture content, ash content, vitamin C content, total soluble solid, crude fiber content, total acid, score of organoleptic values of colour, taste and texture and hedonic of organoleptic values of colour, flavor, taste, and texture. The results showed that ratio of pineapple with broccoli pulps had highly significant effect on vitamin C content, crude fiber content, total acid, score of organoleptic values of colour, taste and texture, and hedonic of  organoleptic values of flavor and texture. Arabic gum concentration had highly significant effect on moisture content, ash content, vitamin C content, total soluble solid, crude fiber content and total acid. Interactions of the two factors had highly significant effect on vitamin C content and had no significant effect on moisture content, ash content,total soluble solid, crude fiber content, total acid, score of organoleptic values of colour, taste and texture, and hedonic of organoleptic values of colour, flavor, taste and texture. The ratio of  pineapple and broccoli  pulps of (55% : 45%) and arabic gum concentration of (1,2%) produced the best quality of fruit leather and accepted by the panelists. Keywords: Arabic gum,Broccoli, Fruit leather, Pineapple